Analisis Penerapan Sistem Informasi Pemerintah Daerah (SIPD) terhadap Kualitas Laporan Keuangan Kota Subulussalam - Silvia Hardianti Manik; Ratna Sari Dewi; Indra Fauzi; Henny Andiyani Wirananda (BADAN PENERBIT STIEPARI PRESS, 2025)
The advancement of information technology has significantly impacted public financial management in Indonesia. To strengthen good governance, which encompasses transparency, accountability, efficiency, and effectiveness, the government introduced the Local Government Information System (SIPD). The implementation of this system is regulated under Minister of Home Affairs Regulation No. 70 of 2019 and further reinforced by Circular Letter No. 500.5.4/48/SJ of 2023, which mandates all local governments to adopt SIPD starting in the 2024 fiscal year. SIPD replaces the Regional Management Information System (SIMDA), which was considered to have limitations in integration, slow processes, and inconsistencies in financial reporting. This study aims to analyze the implementation of SIPD and its impact on the quality of financial reporting at the Human Resources and Development Agency (BKPSDM) of Subulussalam City. The research employs a qualitative descriptive method with a case study design, collecting data through interviews, observations, and documentation. Data analysis uses the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The research informants are employees directly involved in SIPD operations and financial report preparation. The findings indicate that SIPD enhances the quality of financial reporting in four aspects of the Government Accounting Standards (SAP). Relevance improves as reports are more timely and useful for decision-making; reliability increases through automated validation, though network disruptions and system errors remain obstacles; comparability is achieved because SIPD produces standardized national reports; and consistency is strengthened through uniform reporting procedures, thereby improving the credibility of financial information. However, the study also identifies challenges, including limited technical competence among employees, insufficient training, and inadequate infrastructure. These findings suggest that the success of SIPD largely depends on human resource readiness and technological support.